Penerapan Multi-Palette Color untuk Pemberian Saran Pemilihan Warna Tema Desain Visual Vektor - Suliswaningsih; Adam Prayogo Kuncoro; Ali Nur Ikhsan; Muhammad Thoriq Jamil; Syahrul Sani (P3M Politeknik Negeri Cilacap, 2024)
In graphic design, many creative applications offer many templates. This design platform is suitable for creative designers and hobbyists such as marketers, bloggers, social media managers, etc. In a design workflow, users select a template and replace elements with their resources. Instead of creating one color palette for all elements, researchers extract multiple color palettes from each visual element in a graphic document and then combine them into a set of colors. Researchers design sample color schemes to complement color sets and we recommend colors that might be determined based on the color context in a multi-palette. Researchers conducted model training and created a color recommendation system for a collection of vector visual designs. The proposed color recommendation method is targeted to be a color prediction medium, as well as a color recommendation system on vector media. The results of this study are in the form of color recommendations for vector graphic design based on a multi-palette of visual elements.